2018
DOI: 10.1001/jama.2018.8151
|View full text |Cite|
|
Sign up to set email alerts
|

Association of the US Department of Justice Investigation of Implantable Cardioverter-Defibrillators and Devices Not Meeting the Medicare National Coverage Determination, 2007-2015

Abstract: (DOJ) conducted an investigation into implantable cardioverter-defibrillators (ICDs) not meeting the Centers for Medicare & Medicaid Services National Coverage Determination (NCD) criteria. OBJECTIVE To examine changes in the proportion of initial primary prevention ICDs that did not meet NCD criteria following the announcement of the DOJ investigation at hospitals that reached settlements (settlement hospitals) and those that did not (nonsettlement hospitals).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 25 publications
0
8
1
Order By: Relevance
“…Despite initial enthusiasm for LVAD therapy in end stage HF patients, and dramatic improvements in clinical outcomes, clinical use has plateaued at levels far less than previously forecasted [ 9 ]. Our findings offer a potential explanation for this finding—unlike in the case of other therapeutics where real-world use is expanded beyond the population studied in the clinical trial, treatment with LVADs appears to be quite conservative considering the number of patients who are inferred to benefit from this intervention [ 10 12 ]. The causes of this behavior are unclear and might result from several factors such as patient preferences, lack of knowledge among most physicians about the therapy, and misunderstandings regarding candidacy [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite initial enthusiasm for LVAD therapy in end stage HF patients, and dramatic improvements in clinical outcomes, clinical use has plateaued at levels far less than previously forecasted [ 9 ]. Our findings offer a potential explanation for this finding—unlike in the case of other therapeutics where real-world use is expanded beyond the population studied in the clinical trial, treatment with LVADs appears to be quite conservative considering the number of patients who are inferred to benefit from this intervention [ 10 12 ]. The causes of this behavior are unclear and might result from several factors such as patient preferences, lack of knowledge among most physicians about the therapy, and misunderstandings regarding candidacy [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was recently reported that the number of ICDs implanted in the US has fallen significantly since the announcement of the results of the DOJ investigation and repayment process. 4 I take this as a hopeful sign that cardiologists are following the guidelines and implanting these devices appropriately.…”
mentioning
confidence: 98%
“…Firstly, clinical practice is not static as shown by the substantial decrease in the number of primary prevention ICDs and the proportion of devices not meeting the Centers for Medicare & Medicaid Services National Coverage Determination (NCD) criteria following the announcement of a US Department of Justice investigation into ICD use in 2010 [13] . There are also some important limitations of the SHaRe registry itself including the risk of inclusion bias, missing data and a relatively short follow-up period.…”
mentioning
confidence: 99%